A study on clinical analysis and surgical outcomes of occipital encephalocele in children - Parmar, Harisinh V.; Adhvaryu, Nilay S.; Shah, Jaimin K.; Trivedi, Bhargav; Parmar, Milap (International Surgery Journal, 2021)
Background: Occipital encephalocele is the commonest of encephalocele involving protrusion of meningeal and neural structures through the occipital bone defects. It is a congenital anomaly with varied presentation and can include only meninges to the cerebellum, medulla, venous sinus and brainstem structure. Methods: Study was done at civil hospital Ahmedabad from January 2017 to January 2020 occipital encephalocele patients were operated at the department of neurosurgery. The patients were evaluated by computed tomography scan of the brain, magnetic resonance imaging and ultrasound. The operated cases were reviewed and relevant data such as age, sex, location of encephalocele, the size of the lesion, operative method, seizure and hydrocephalus along with postoperative complications were recorded for analysis. Results: In our study, we have better results in contrast to literature may be due to absence of hydrocephalus, other anomalies of brain, seizure disorder and lack of functional brain tissue within the sac as these factors has been associated with poor neurological outcome. Out of 35 operated, 2 patients expired of which 1 patient had other complication at presentation and other one had had developed cerebrospinal fluid (CSF) leakage with ventriculitis. Conclusions: Repair of encephaloceles should be ideally done in the postnatal period to minimize risks of ulceration and trauma to the lesion with subsequent meningitis. We can conclude that folic acid supplementation should be strongly emphasized in health centres to reduce these neural tube defects as none of the patients in our study has taken.